Agent-based modelling and simulation in the irrigation management sector: applications and potential - Tzima F.A.; Athanasiadis N.; Mitkas P.A. (Water saving in Mediterranean agriculture and future research needs [Vol. 2], 2007)
Several models attempt to address the problem of common-pool resources, especially in the case of irrigation management. In fact, the latter task represents a great challenge for researchers and decision makers, as it has to cope with various water-related activities and conflicting user perspectives within a specified geographic area. Simulation models, and particularly Agent-Based Modelling and Simulation (ABMS), can facilitate overcoming these limitations: their inherent ability of integrating ecological and socio-economic dimensions, allows their effective use as tools for evaluating the possible effects of different management plans, as well as for communicating with stakeholders. Our current study of agent-based models for irrigation management draws some interesting conclusions, regarding the geographic and representation scale of reviewed models, as well as the degree of stakeholder involvement in the various development phases. Such tools, when effectively capturing social interactions and coupling them with environmental and economical models, can promote active involvement of interested parties and produce sustainable and approvable solutions to irrigation management problems.
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)